ICT tools patterns of use among Malaysian ESL undergraduates - Siew Ming Thang; Kean Wah Lee; Puvaneswary Murugaiah; Nurjanah Mohd Jaafar; Choon Keong Tan; Nurul Iman Ahmad Bukhari (Universiti Kebangsaan Malaysia, 2016)
The proposal to undertake major reforms in universities to cater to the need of the so-called “digital natives” has revealed the belief that there is a homogenous generation of university students highly skilled in the usage of technology is untrue. Instead these students seem more inclined to use technology for social rather than academic purposes. In Malaysia, the use of technology in learning English as Second Language (ESL) has generally been well received. However the characteristics of the “digital natives” have not been clearly defined until recently when Thang et al. (2014) undertook a study to investigate patterns of ICT use of students in a public university in Malaysia. Their findings are somewhat similar to those of other countries but they differ in that they found students show a preference for the teachercentred approach. The current study extends on this by undertaking a study involving four different types of public universities. A questionnaire designed by the research team was used to collect data which were analysed quantitatively using SPSS. The findings revealed that students from all four universities generally felt that technology is useful for learning ESL. However, their usage is more for recreation than for learning ESL. It further revealed that the teachers used technology only moderately, but the students still felt that their teachers are competent in the use of technology. This shows their unwillingness to criticize their teachers openly. However, there were some variations which suggest that students from older research universities are more self-reliant and students from newer universities are more receptive to the use of technology for learning ESL.